Sonomammography in Neonatal Mastauxe - Sushil Ghanshyam Kachewar; Smita Sushil Kachewar (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2015)
Prominence or even enlargement of one or both breasts is known in neonates. It is believed to be a physiological response to falling levels of maternal estrogen towards last trimester of pregnancy. This input stimulates prolactin release from the newborn's pituitary leading to transient neonatal breast enlargement. This phenomenon is independent of the gender of the neonate. It presents in the first few weeks of life and resolves subsequently. Often fluid discharge is noted from the prominent or swollen breast that resolves without treatment in subsequent weeks. Manual breast manipulation for discharge removal may lead to undesirable effects like local irritation, enhanced enlargement, prolonged tissue hypertropy or even mastitis. A case of such 7-days female neonate is presented here backed with imaging evaluation for confirmation of diagnosis. Typical sonomammographic findings are described. [Cukurova Med J 2015; 40(Suppl 1): 22-24]